Investigating the Influence of Management Factors on Labour Productivity of Tea Pluckers in the Ratnapura District of Sri Lanka - L. S. Hemapala; L. Wijewardene (Investigating the Influence of Management Factors on Labour Productivity of Tea Pluckers in the Ratnapura District of Sri Lanka, 2024)
The tea industry contributes to the Sri Lankan economy through employment opportunities, national output and foreign exchange earnings. Tea pluckers in Sri Lanka act as key players in supplying tea for the domestic and foreign tea markets. This study investigates the influence of management factors on the labour productivity of tea pluckers in the Ratnapura district of Sri Lanka. The study adopts the quantitative analysis of management factors that can impact the labour productivity of the tea pluckers such as operational management factors, human resource management factors and financial management factors. Factors influencing the labour productivity of tea pluckers in the Ratnapura district of Sri Lanka were determined by using multiple regression analysis. Three vital factors consisting of operational management factors, human resource management factors and financial management factors were examined. Based on data from a Google survey of 250 tea pluckers, financial management factors have influenced the labour productivity of the tea pluckers in the Ratnapura district of Sri Lanka while operational management factors and human resource management factors have no influence on the labour productivity. These results are relevant for developing countries because tea pluckers are one of the key drivers of economic development. Understanding links between management factors and the labour productivity of tea pluckers is important for tea pluckers, tea smallholders, tea exporters, and policymakers. It will also help to promote certain management factors by directing scarce resources to tea pluckers. Decision-makers and relevant authorities in Sri Lanka’s government should make effective policies for tea pluckers; then investors, smallholders, tea institutions, societies and tea factories can invest and pay attention to tea pluckers.